Samuel Pufendorf disciple of Hobbes for a re-interpretation of modern natural law - Palladini, Fiammetta (Brill, 2020)
Part 1. Pufendorf the Hobbesian -- I The Theory of Obligation -- II Nature of Man and State of Nature: the Doctrine of Sociality -- Part 2. Why Did Pufendorf Pass for an Anti-Hobbesian? -- I Pufendorf's Place in the History of Ethics According to Pufendorf -- II The Role of Cumberland -- III Anti-Hobbesian Aspects of the Elementa -- IV The Barbeyrac Factor
Mit Registern ("Table of passages cited", "Index of names")
Keywords: Pufendorf, Samuel von -- 1632-1694; Hobbes, Thomas -- 1588-1679; Rezeption; Naturrecht; Hobbes, Thomas / 1588-1679; Pufendorf, Samuel / Freiherr von / 1632-1694; Hobbes, Thomas (1588-1679); Pufendorf, Samuel (Freiherr von; 1632-1694); Natural law